PENGARUH MOTIVASI DAN LITERASI KEUANGAN TERHADAP MINAT BERINVESTASI DI PASAR MODAL - Yois Shofwa S (Jurnal Penelitian Agama, 2017)
Abstract: The economic development causes everyone to have the ability to manage their financial assets. OJK survey results concluded that the lower social strata the lower the level of literacy. Thus the Financial Services Authority (OJK) with the Financial Services Industry (IJK) will continue to encourage and implement literacy programs and financial inclusion to target the financial inclusion index. One of the most targeted groups of society is the academics in both schools and universities. In 2016, Indonesia Stock Exchange (IDX) Yogyakarta Branch is moving to increase public investment in capital market by preceded by financial literacy program. In cooperation with OJK and several Capital Investment Companies held socialization at several universities in Central Java and Yogyakarta. The activity was followed up by OJK Purwokerto at gebyar syariah event to increase Banyumas community investment interest. At the event, Banyumas district won two records from the World Record Museum of Indonesia or MURI. The record is the Creation of Shariah Fund Investors Category of Public Society of 5,546 people and the Shariah Investor Generation in the highest one as many as 2,000 people. The university that obtained the MURI record is Muhammadiyah University of Purwokerto. The purpose of this research is to know whether there is any influence of financial literacy and motivation to investment interest in capital market. The method of analysis used in this study is Multiple Linear Regression Analysis with hypothesis testing using t test and F test. The result when connected with the results of F test found that the variables of financial and motivation simultaneously or together influence the investment interest. Keywords : motivation, financial literacy, capital market